2021
DOI: 10.1101/2021.02.04.21251087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staff-Pupil SARS-CoV-2 Infection Pathways in Schools: A Population Level Linked Data Approach

Abstract: Background: Better understanding of the role that children and school staff play in the transmission of SARS-CoV-2 is essential to guide policy development on controlling infection whilst minimising disruption to children's education and wellbeing. Methods: Our national e-cohort (n=500,779) study used anonymised linked data for pupils, staff and associated households linked via educational settings. We estimated the risk of testing positive for SARS-CoV-2 infection for staff and pupils over the period August… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Modeling predicts that when schools open, 5%–24% of schools would have at least 1 person with active COVID-19, with transmission mitigated by hybrid attendance [ 5 ]. A Wales study found a 12% increase in the odds of testing positive within year groups, with pupil–pupil transmission linked to schools [ 6 ]. A meta-analysis found decreasing severe acute respiratory syndrome coronavirus 2 transmission with increasing distance, with measurable difference between 3 and 6 feet [ 7 ].…”
mentioning
confidence: 99%
“…Modeling predicts that when schools open, 5%–24% of schools would have at least 1 person with active COVID-19, with transmission mitigated by hybrid attendance [ 5 ]. A Wales study found a 12% increase in the odds of testing positive within year groups, with pupil–pupil transmission linked to schools [ 6 ]. A meta-analysis found decreasing severe acute respiratory syndrome coronavirus 2 transmission with increasing distance, with measurable difference between 3 and 6 feet [ 7 ].…”
mentioning
confidence: 99%